Safety as a factor of social and economic development under globalization conditions - Łuczyszyn, Andrzej (Bezpieczeństwo jako czynnik rozwoju społeczno-gospodarczego w warunkach globalizacji, 2020)
Contemporary social and economic development (regional and local) occurring under very dynamic conditions triggered mostly by globalization requires effective and professional safety- -targeted actions aiming at stabilising undesirable threats as well as to develop safety strategies. This is crucial as a safety category requires its adaptation to each and every social and economic reality which subsequently confirms its flexibility and evolution. This is directly related to the economic policy being created which is going to use features of the Polish economy and society, which are to provide a competitive advantage over other economies and denotes that in conditions of a new service-oriented economy, safety is becoming the most significant element of development. This factor cannot be omitted in any strategic documents that constitute specific procedures determining the category of national security. Undoubtedly, however, it appears to be increasingly deficient in these sectors of socio-economic life, in which there is increasing social disorientation, and thus the risk increases
Biblioteka Regionalisty, 2020, Nr 20, s. 79-89
Keywords: social and economic development; safety; globalization; rozwój społeczno-gospodarczy; bezpieczeństwo; globalizacja